155k views
5 votes
Use the substitution method to solve the following system of equations: 3x + 5y = 3 x + 2y = 0 (1 point) (1, 1) (6, −3) (6, 1) (1, −3)

User GoalBased
by
4.0k points

2 Answers

3 votes

Answer:

(6,-3)

Explanation:

Got it right on the test

Hope this helps :)

User Bryan Dannowitz
by
4.4k points
3 votes

Explanation:

Given.


3x+5y=3


x+2y=0

Take the second equation and subtract 2y to both sides.


(x+2y)-2y=0-2y


x=-2y

Substitute x into the first equation and simplify.


3x+5y=3


3(-2y)+5y=3


-6y+5y=3


-y=3

Invert.


y=-3

Substitute Y into your second equation.


x+2y=0


x+2(-3)=0


x-6=0

Add -6 to both sides.


(x-6)+6=0+6


x=6

Answer:

(6, -3)

User Dmitriy Tarasov
by
5.5k points